The Influence of Business Studies Teachers’ Competency on Students’ Academic Achievement - Kolandan, Subramaniam; Raman, Arumugam; Yusof, Fahainis Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The wave of Industry Revolution 4.0 has opened up the window for more job opportunities with the advent of new technology-driven careers. Therefore, the education sector must be more proactive in producing a smart and knowledgeable generation in the business world, rendering teachers as the backbone behind the Ministry of Education’s aspiration towards empowering the sector in the country. In other words, the teachers play a very important role in student development, whereby student achievement is closely related to the quality and ability of their teachers, who are tasked with teaching them and sparking their interest in learning. Accordingly, the subject of Business Studies offered needs to be in line with the current economical wave and the teachers should thus master all components illustrated in Mc Ber’s Iceberg Competency Model, namely knowledge, skill, and professionalism. Therefore, the population for this study consisted of all Form Six teachers who were teaching Business Studies either in high school or Form Six colleges. The current study focused on three states located in the Northern Zone of Peninsular Malaysia, namely Perlis, Kedah, and Penang. The findings showed that all three components of the competency model were positive and significant to student achievement on a modest-to-weak scale. Meanwhile, other factors may also play a more important role in measuring student achievement in this subject.